2016
DOI: 10.1002/ajim.22559
|View full text |Cite
|
Sign up to set email alerts
|

Economic consequences of workplace injuries in the United States: Findings from the National Longitudinal Survey of Youth (NLSY79)

Abstract: Occupational injuries exacerbate income inequality. Efforts to reduce such disparities should include workplace safety and health enforcement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 29 publications
0
20
0
3
Order By: Relevance
“…Work in construction and other blue‐collar occupations is more physically demanding as well as more hazardous. Sustained work‐related illness or injury among workers in those occupations may have long‐term negative impact on both self‐reported health and income [Dong et al, , ]. Risk of more severe outcomes from some injuries, such as fall injuries, also escalates among older workers and older workers may require longer recovery times [CPWR, ; U.S. Bureau of Labor Statistics, ].…”
Section: Discussionmentioning
confidence: 99%
“…Work in construction and other blue‐collar occupations is more physically demanding as well as more hazardous. Sustained work‐related illness or injury among workers in those occupations may have long‐term negative impact on both self‐reported health and income [Dong et al, , ]. Risk of more severe outcomes from some injuries, such as fall injuries, also escalates among older workers and older workers may require longer recovery times [CPWR, ; U.S. Bureau of Labor Statistics, ].…”
Section: Discussionmentioning
confidence: 99%
“…Kecelakaan kerja di Indonesia menurut sektor masih didominasi oleh sektor manufaktur serta konstruksi dengan porsi sebesar 32% yang kemudian dilanjutkan oleh sektor lainnya seperti sektor transportasi (9%), sektor kehutanan (3,8%), sektor pertambangan (2,6) serta sektor-sektor lainnya sebesar 20,7%. (Jamsostek, 2014) Besarnya persentase jumlah kecelakaan kerja pada sektor industri manufaktur tentunya berimplikasi peningkatan biaya bukan hanya kepada pekerja serta keluarganya, namun juga kepada perusahaan, salah satunya berupa tunjangan kecelakaan kerja (Dong, Wang, Largay, & Sokas, 2016). Peningkatan biaya tersebut juga dapat berimplikasi kepada penurunan keuntungan perusahaan (Shalini, 2009 Strategi utama yang dapat dilakukan oleh perusahaan untuk mengurangi tunjangan kecelakaan kerja yang dikeluarkan perusahaan yaitu melalui pengendalian jumlah kecelakaan kerja (Bernacki, Tao, & Yuspeh, 2010).…”
Section: Gambar 1 Jumlah Kasus Kecelakaan Kerja DI Indonesia Sumber unclassified
“…Peningkatan biaya tersebut juga dapat berimplikasi kepada penurunan keuntungan perusahaan (Shalini, 2009 Strategi utama yang dapat dilakukan oleh perusahaan untuk mengurangi tunjangan kecelakaan kerja yang dikeluarkan perusahaan yaitu melalui pengendalian jumlah kecelakaan kerja (Bernacki, Tao, & Yuspeh, 2010). Hal tersebut dikarenakan tunjangan kecelakaan kerja itu terdiri dari frekuensi kecelakaan kerja yang terjadi, dikalikan dengan tingkat keparahan kecelakaan kerja itu sendiri (Dong et al, 2016), sehingga pengurangan jumlah kecelakaan kerja akan berdampak kepada penurunan tunjangan kecelakaan kerja. Pengurangan tingkat kecelakaan kerja juga dapat menurunkan gangguan pada sektor produksi yang berimbas kepada peningkatan produktivitas perusahaan (Zou, Shi, & Li, 2010).…”
Section: Gambar 1 Jumlah Kasus Kecelakaan Kerja DI Indonesia Sumber unclassified
See 1 more Smart Citation
“…Keall and colleagues [8] found that the annual social cost of unintentional home injuries was more than threefold that of the annual social cost of road injury. Moreover, workers who return after experiencing injuries may have lower wages [9]. Furthermore, injury experience may degrade cognitive ability which may later affect the capacity to work [10].…”
Section: Introductionmentioning
confidence: 99%